2012
DOI: 10.4319/lo.2012.57.1.0235
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling food quantity and quality effects in zooplankton response to P‐enrichment and UV radiation

Abstract: In a 32-yr record in oligotrophic Lake La Caldera (Sierra Nevada, Spain) biomass of zooplankton was strongly correlated with precipitation, aerosol deposition intensity, and ultraviolet radiation (UVR). The food associatedeffects of these factors for zooplankton growth were tested in field-laboratory experiments with the aim of separating the effects of food quantity from those of food quality at low food conditions, where there is good evidence to support the existence of food quality effects. Manipulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…copepods would not be expected to respond to the P and N content of the seston. However, copepods showed strong growth response to food P content at low food quantity, consistent with recent observations of a strong relationship between Mixodiaptomus laciniatus growth and seston P content in this ultraoligotrophic lake (Villar-Argaiz et al 2012). If copepods with complex life cycles and high C:N:P ratios suffer growth penalties due Table 4 and Results section for statistical results.…”
Section: Discussionsupporting
confidence: 91%
“…copepods would not be expected to respond to the P and N content of the seston. However, copepods showed strong growth response to food P content at low food quantity, consistent with recent observations of a strong relationship between Mixodiaptomus laciniatus growth and seston P content in this ultraoligotrophic lake (Villar-Argaiz et al 2012). If copepods with complex life cycles and high C:N:P ratios suffer growth penalties due Table 4 and Results section for statistical results.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have shown that temperature in combination with other environmental variables can affect zooplankton populations ( e.g. 4,20–22). Other studies have examined the interaction of temperature and UVR (8,9,23).…”
Section: Introductionmentioning
confidence: 99%
“…), which provide most of the high quality food for herbivore growth and this may contribut to the surface blooms of copepoda and rotifera (Villar‐Argaiz et al. ). In addition, some highly adaptable or opportunistic consumers (ciliophora) can grow in both layers because of its stronger ability of movement and applicability (Pfister et al.…”
Section: Discussionmentioning
confidence: 99%
“…Copepoda and rotifera had a cosmopolitan distribution in freshwater where they feed on small fragments of plant material, phytoplankton or carrion (Miracle 1982;Boothroyd et al 2002). The surface water is rich in productive primary producer and microplankton (Iriarte et al 2000;Schelske et al 2003), which provide most of the high quality food for herbivore growth and this may contribut to the surface blooms of copepoda and rotifera (Villar-Argaiz et al 2012). In addition, some highly adaptable or opportunistic consumers (ciliophora) can grow in both layers because of its stronger ability of movement and applicability (Pfister et al 2002).…”
Section: Zooplankton Dominance In Surface Layermentioning
confidence: 99%